Three-dimensional simulations of the expanding remnant of SN 1987A. Issue Volume 9:Issue S296(2013) (29th January 2014) - Potter, Toby; Staveley-Smith, Lister; Kirk, John; Reville, Brian; Bicknell, Geoff; Sutherland, Ralph; Wagner, Alexander; Zanardo, Giovanna
Abstract: SNR 1987A is the expanding remnant from the brightest supernova since the invention of the telescope. The remnant has been monitored extensively in the radio at variety of wavelengths and provides a wealth of data on which to base a simulation. Questions to be answered include estimating the efficiency of particle acceleration at shock fronts, determining the cause of the one-sided radio morphology for SNR 1987A and investigating the gas properties of the pre-supernova environment. We attempt to address these questions using a fully three-dimensional model of SNR 1987A.